The Students' Problems in the Paragraph Writing Course at Universitas Negeri Makassar - Sakkir, Rini Isnaeni; Muh. Tahir; Sofyan, Ryan Rayhana (International Journal of Language, Education, and Literature, 2025)
This study investigates the challenges faced by second-year students in the Paragraph Writing course at Universitas Negeri Makassar. The research identifies key difficulties such as understanding course materials, generating ideas, grammar issues, time management struggles, and difficulties with implementing lecturer feedback. The findings offer valuable insights into the specific problems that hinder student success in this course, contributing to the understanding of writing difficulties in an English as a Foreign Language (EFL) context. The study aims to provide a more comprehensive understanding of the problems that students face and seeks to make recommendations for addressing these obstacles.